Optimizing the Enforcement of Asset Forfeiture as an Additional Penalty for Corruption Offenders to Recover State Losses: Optimalisasi Penerapan Pidana Tambahan Perampasan Aset terhadap Koruptor sebagai Upaya Pemulihan Kerugian Negara - Salsabila, Syana Mifta; Waluyo, Bambang (Universitas Muhammadiyah Sidoarjo, 2025)
Corruption continues to generate substantial state losses in Indonesia, while enforcement strategies still prioritize imprisonment over effective asset recovery, leaving illicit proceeds beyond the reach of the state. This study aims to evaluate the legal framework and enforcement barriers of asset forfeiture as an additional penalty for corruption and to assess the reform potential of non-conviction based asset forfeiture for accelerating recovery of state losses. Using a normative juridical design, the research applies statutory and conceptual approaches through systematic analysis of the Indonesian Criminal Code, anti-corruption legislation, anti-money laundering provisions, and the Draft Law on Asset Forfeiture of Criminal Acts. The study finds that although asset forfeiture is legally recognized, implementation remains weak due to integrity deficits in law enforcement, fragmented legal instruments, and limited operational effectiveness in tracing and confiscating proceeds of corruption. As a result, asset recovery outcomes are frequently suboptimal and deterrence effects are diluted. The key novelty is the policy argument that a comprehensive non-conviction based asset forfeiture regime, as advanced in the draft legislation, can enable confiscation of illicit assets even when criminal conviction is unattainable, thereby closing enforcement gaps that conventional conviction-based forfeiture cannot address. The findings imply that legal reform should institutionalize non-conviction based asset forfeiture alongside stronger due process safeguards, interagency coordination, and anti-money laundering alignment to improve corruption deterrence and measurably increase recovery of state losses. Highlights: Current forfeiture enforcement gaps sharply limit corruption asset recovery and state loss restitution. Non-conviction based forfeiture enables confiscation when prosecution fails through death, flight, or absconding. Comprehensive forfeiture legislation strengthens due process, interagency coordination, and corruption deterrence outcomes Keywords: Non-Conviction Based Forfeiture, Asset Recovery, Corruption Deterrence, Financial Crime Governance, Anti-Money Laundering, Legal Reform